Strategies for effective training evaluation (IPE-UNDP experience) - Reddy, B. Ratan (2002)
The article is based on the author's experience in organising 3-weeks - six Management Development Programmes being sponsored by Public Sector Restructuring and Internal Audit Board, Kerala (UNDP Project on Public Sector Reforms) for strategic, Management and Supervisory Cadre of M/s Auto Kaust Ltd. M/s Kerala State Drugs and Pharmaceuticals Ltd., and Kerala Salicyletes and Chemicals Ltd., Kerala. The strategy adopted in these programmes was "Training as a Tool for Turnaround" an innovative strategic tool. This paper is a result of such discomfort felt by the author during his experience in assessing training and development systems, conducting training need assessment, as well as designing and conducting training programmes with specific strategic objectives of the organisation. The approach presented here namely Strategic Evaluation and Assessment of Training System (SEATS) is based on practical experience. - Reproduced.
Keywords: Training